Human rights in international relations - Forsythe, David P. (Cambridge University Press, 2000)
This new textbook provides an introduction to human rights in international relations at the turn of the twenty-first century. The book examines the policy-making process that establishes and tries to apply human rights norms through the United Nations, regional organizations, state foreign policy, human rights groups, and transnational corporations. Four themes permeate the book: that human rights are here to stay in international relations, that state sovereignty is being transformed by the human rights discourse, that the 'soft' law of diplomacy is as important as the 'hard' law of court judgments, and that private actors are highly important in international human rights developments. The book documents the many changes in international human rights during the past half-century, and considers the future of universal human rights. Containing chapter-by-chapter guides to further reading and discussion questions, this book will be of interest to all undergraduate and graduate students of human rights, and their teachers.